A preliminary study on the uses of gadgets among children for learning purposes - Zuraina, Ali; Ahmad Mahfuz, Mohamed Anuar; Nurul Atikah, Mustafa; Khairun Nisa, Abdul Halim; Kasturi, Sivabalan (IOP Publishing, 2020)
The study explores the uses of gadgets to assist young learners in their quest for learning. More specifically, the aims of the current study are to identify the gadgets that are used among children for learning purposes, hours they spend in using the gadgets, rules that are being implemented by parents for the uses of gadgets, benefits gain by children in the uses of the gadgets and parents' expectations of the uses of the gadgets for learning purposes. The study that employs qualitative research among six respondents found that smartphones, tablets and computers were among the gadgets that were used by the children when parents permitted them to use the tools on average for three hours. It was also observed that some parents were rigid while some were lenient setting rules for their children to use the gadgets. Various perceived benefits were also demonstrated among parents. In terms of expectations, parents demonstrated some hope that the uses of the gadgets among their children would make the latter able to learn language, mathematics and social skills; to name a few. The study implies that parents need to control the uses of gadgets among their children even though the tools are used for learning purposes.